Tunable Delivery of siRNA from a Biodegradable Scaffold to Promote Angiogenesis In Vivo. (16th December 2013) - Nelson, Christopher E.; Kim, Arnold J.; Adolph, Elizabeth J.; Gupta, Mukesh K.; Yu, Fang; Hocking, Kyle M.; Davidson, Jeffrey M.; Guelcher, Scott A.; Duvall, Craig L.
Abstract : A system is engineered for temporally controlled delivery of siRNA from biodegradable tissue regenerative scaffolds. Therapeutic application of this approach to silence PHD2 promotes expression of pro‐angiogenic genes controlled by HIF1α and enhanced scaffold vascularization in vivo. This technology provides a new standard for efficient and controllable gene silencing to modulate host response within regenerative biomaterials.